2018
DOI: 10.3390/en11051140
|View full text |Cite
|
Sign up to set email alerts
|

Unit Commitment Towards Decarbonized Network Facing Fixed and Stochastic Resources Applying Water Cycle Optimization

Abstract: This paper presents a trustworthy unit commitment study to schedule both Renewable Energy Resources (RERs) with conventional power plants to potentially decarbonize the electrical network. The study has employed a system with three IEEE thermal (coal-fired) power plants as dispatchable distributed generators, one wind plant, one solar plant as stochastic distributed generators, and Plug-in Electric Vehicles (PEVs) which can work either loads or generators based on their charging schedule. This paper investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Results synopsis for GSA and Dynamic Programming (DP) (implicating emission cost and losses of the system). Considering losses of IEEE 30 bus system and comparing the obtained results in Table 7 with Table 8 in Reference [31] without considering transmission line losses, it is found that:…”
Section: Scenario 4 (Rers Pevs and The Three Coal-fired Units)mentioning
confidence: 99%
“…Results synopsis for GSA and Dynamic Programming (DP) (implicating emission cost and losses of the system). Considering losses of IEEE 30 bus system and comparing the obtained results in Table 7 with Table 8 in Reference [31] without considering transmission line losses, it is found that:…”
Section: Scenario 4 (Rers Pevs and The Three Coal-fired Units)mentioning
confidence: 99%
“…WCA is one of the promising heuristic optimization techniques especially in power system area. WCA has been introduced to solve optimal microgrids integration considering emission cost, reliability and loss minimization [11][12][13][14]. Gravitational Search Algorithm is another heuristic-based optimization technique that has been implemented for scheduling, sizing and citing of DGs [15][16][17][18][19][20].…”
Section: Pgmentioning
confidence: 99%
“…Gravitational Search Algorithm is another heuristic-based optimization technique that has been implemented for scheduling, sizing and citing of DGs [15][16][17][18][19][20]. Compared to the previously reported work which only considers either RERs [10] or PHEVs [13] in the scheduling problem, this paper augments the RER with PHEVs, together with the impact of weekly variation of loads, RER profile and SOC of PHEVs. As such, this paper presents a comprehensive unit commitment model compared to previous work.…”
Section: Pgmentioning
confidence: 99%
“…The Cuckoo search algorithm will determine the size and location of the DGs. [15] The algorithm is done on "MATLAB© R2017b coding". Work is done on an A1278 Macbook 2.0 GHz Core 2 Duo (P7350) 2GB RAM, 256 MB VRAM 160GB GHH storage and 8X DL "SuperDrive"…”
Section: Load Flowmentioning
confidence: 99%